‘Selfies’ Under Quarantine: Exploring Networked Emotions in the Time of ‘Social Distancing’ - Della Ratta, Donatella (Imaginations)

(untitled) (York University, 2021)
This essay focuses on auto-ethnography and auto-fiction as USEFUL tools to reflect on the ways in which networked identities are reshaped and reconfigured within the context of a global pandemic where social relationships, family life, work routines, and learning processes are increasingly migrating to the online domain. The piece builds upon the experience of an undergraduate class who collectively contributed to the blog series ‘Selfies Under Quarantine’ during the first severe lockdown in March 2020. It discusses the question of methods and suggests looking at the ‘draft’ as both an aesthetics and an ethics to navigate the current context of crisis.